تصميم وحدات دراسية في علم البيان باستخدام المدونة الإلكترونية لطلبة قسم اللغة العربية وآدابها بالجامعة الإسلامية العالمية بماليزيا: دراسة وصفية تحليلية = The design of computer assisted lessons in the science of al-Bayan using blog for students at Department of Arabic Language and Literature, International Islamic University Malaysia: a descriptive and analytical study - Awang Ali, Mohammad Amnan; Sahrir, Muhammad Sabri; Aminordin, Nor Amira (Pusat Pengajian Teras (PPT), KUIS, 2020)
تسعى هذه الدراسة إلى مساعدة الطلاب المتخصصين في اللغة العربية بالجامعة الإسلامية العالمية بماليزيا في تعلّم علم البيان، وذلك عن طريق تصميم وحدات دراسية بلاغية حاسوبية باستخدام المدونة الإلكترونية. وانتهجت هذه الدراسة المنهجين الوصفي والتحليلي، إذ تطلّب المنهج الوصفي من الباحثين أنْ يجمعوا المعلومات عن علم البيان، وكذلك نظريّات التعلّم باستخدام المدوّنة الإلكترونية. وتتوزّع الإجراءات العمليّة للتحليل على عدة مراحل، وهي: تحليل حاجات الدارسين قبل القيام بتصميم الوحدات، وتحليل آراء الخبراء ومراجعتهما أثناء التصميم، وتحليل نتائج الاختبار القبلي والاختبار البعدي لدى الدارسين قبل وبعد القيام بالتجريب، وأخيرًا تحليل نتائج التقويم التكويني لدى الدارسين. وقد قام الباحثون بتصميم هذه الوحدات الدراسية باستخدام المدوّنة الإلكترونية، وفقًا لآ راء الدارسين )(ADDI لتطويره على نموذج أدي ومقترحاتهم وحاجاتهم. وتمّ اختيار العينة لهذه الدراسة من طلبة قسم اللغة العربية وآدابها بالجامعة الإسلامية العالمية بماليزيا، وقد بلغ عدد الطلبة المشاركين في التقويم ) 60 ( طالبًا وطالبةً، حيث كان ) 27 ( منهم في تحليل الحاجات، و ) 33 ( منهم في الاختبار القبلي والبعدي، وكذلك في التقويم التكويني للبرنامج. وقد شارك في هذه الدراسة خبيران من الجامعة الإسلامية العالمية بماليزيا، الأوّل في مجال تعليم اللغة العربية بمساعدة الحاسوب وتكنولوجيا التعليم، والآخر في مجال البلاغة العربية. وفي نهاية الدراسة، توصّل البحث إلى نتائج عديدة، ومن أهمها: أغلبية الدارسين لهم رؤية إيجابية عن تعلّم علم البيان عبر المدوّنة الإلكترونية، وقد ارتفعت رغباتهم ودوافعهم، وكذلك تحسّن فهمهم وأداؤهم الدراسي في علم البيان. ****************************************************************************** The purpose of this study is to help Arabic language learners at the Department of Arabic Language and Literature of International Islamic University Malaysia (IIUM) in learning ‘Science of al-Bayan’ by designing a prototype courseware for them. This study was conducted by using systematic descriptive and analytical methodologies, where the descriptive approach required the researcher to gather information about ‘Science of al-Bayan’ and theories of learning through an educational blog. In addition, there were several stages of scientific procedures in the analytical approach. First and foremost, learners’ needs analysis was conducted before the phase of design. Secondly, experts’ review analysis was conducted during the design phase. The next stage was the analysis of the results of pre- and post-tests done by learners. Lastly, the analysis of formative evaluation by the learners after the completion of the development phase was also conducted. A special prototype courseware in learning ‘Science of al-Bayan’ was designed by using an educational blog, based on ADDIE instructional design model in the design and development process based on students’ needs, opinions and suggestions. The participants of this study were 60 students (27 students were selected during the needs analysis phase and 33 students were chosen during the pre- and post-tests and also during the evaluation phase). Two experts were selected from the field of Computer Assisted Instruction (CAI) and Arabic Rhetoric during the needs analysis phase. The results of this study showed that the majority of the students were positive about learning ‘Science of al-Bayan’ through the educational blog which increased their learning desires and motivation, while at the same time improved their understanding and performance in learning this subject.